2014
DOI: 10.1016/j.proeng.2014.06.307
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Wetting of Hydrophobic and Hydrophilic Surfaces–Modelling by Lattice Boltzmann Method

Abstract: Anisotropic wetting on unidirectionally textured surfaces was investigated by Lattice Boltzmann Method. Previously published experimental data were used to validate the numerical model. New analysis were carried out by changing static contact angle of grooved surfaces from hydrophilic to hydrophobic (θ s = 50 − 150 • ). Presented results suggests that anisotropic wetting on unidirectionally textured surfaces is governed by spreading along the grooves by capillary action and mainly is dominant in Wenzel state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
5
21
0
Order By: Relevance
“…Nevertheless,  on GF30 surface is much smaller than that on AA6061 surface. It is basically consistent with simulation results [43]. The different  are mainly caused by the two wetting states.…”
Section: Relationship Between Roughness and Anisotropic Wettingsupporting
confidence: 92%
“…Nevertheless,  on GF30 surface is much smaller than that on AA6061 surface. It is basically consistent with simulation results [43]. The different  are mainly caused by the two wetting states.…”
Section: Relationship Between Roughness and Anisotropic Wettingsupporting
confidence: 92%
“…Consistent with literature, the CA depends on both the chemical properties and the surface roughness. The two common models for describing the wettability of surfaces are by Wenzel and Cassie and Baxter [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kubiak at al. [32] suggested that the Wenzel model is suited for use on hydrophilic surfaces and the Cassie-Baxter model for hydrophobic surfaces. Again, as the current materials are between both models, it is rather difficult to properly assign a specific model for a description of the CA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that high surface quality promotes friction damage [32]. Kubiak et al [30,[33][34][35] report that surface geometry influences friction conditions due to the increased contact force on rough surfaces [36]. This makes it possible to control the friction between the partial slip (only the outer contact area is exposed to the slip, while the central area remains in an adhesive state) and the total slip (the entire contact surface is exposed to the slip).…”
Section: Resultsmentioning
confidence: 99%